The usage of thermal remote sensing in the field of crisis information - examples from the European PHAROS project and the thermal analysis of the 2014/15 Holuhraun fissure eruption - Strobl, Christian; Plank, Simon Manuel; Riedlinger, Torsten (2016)
Thermal remote sensing is providing valuable information in the context of modern crisis information applications supporting disaster management. At the German Remote Sensing Data Center (DFD) of DLR, a wide variety of different sensors are used for the near-real time detection of thermal hot spots over Europe (e.g. MODIS, MSG Seviri) and also for the reprocessing of historic time series (AVHRR). In addition, high resolution satellite imagery (optical/radar) is used by the Center for Satellite Based Crisis Information (ZKI) of DFD to create rapid information (maps and services) about the geographic reference, the disaster extent, the damage assessment and in some cases also for monitoring disastreous fires over time. This paper focuses on two specific crisis related use cases of thermal remote sensing, namely the development of an early warning system for wildfires in Europe and satellite based volcano monitoring in Iceland. The early warning system was developed in the PHAROS project (Multi-Hazard Open Platform for Satellite Based Downstream Services) which aims at the design and development of a modular and scalable multi-hazard open service platform. While this service platform is designed to be multi-hazard, the use case for the pre-operational system was restricted to the forest fire scenario. One of the main concerns is to provide fire hot spots (MODIS, MSG Seviri) as an input for the PHAROS simulation service. Furthermore, EO-based rapid mapping products are used on the short term in support of the fire fighters and in long term for mitigation and preparedness tasks. For the volcano monitoring the Holuhraun fissure eruption in 2014/15 is described. This eruption was one of the largest volcanic events in modern Icelandic history. It is a dike intrusion, that originated from the Islandic Bardarbunga Volcano. Landsat-8 night time acquisitions, MODIS imagery and data from DLR’s TET-1 (Technology Experiment Carrier) are analysed to measure the temperature of the lava over time to show the temporal evolution of ...